PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN DAN REWARD TERHADAP KINERJA DENGAN MEDIASI MOTIVASI PEGAWAI PADA POLITEKNIK NEGERI MALANG - Fredy Perdana Anggara Selfiyan; Ernani Hadiyati; Nugroho Agus Santoso (Jurnal Istiqro, 2023)
This study aims to determine and analyze the effect of implementing MIS and reward on employee performance with motivation as a mediating variable.This research is categorized as an explanatory research with quantitative methods which is defined as a method based on the positivism philosophy. The sample of data in this study was calculated by using the Slovin formula, with 107 out of 147 employees of Civil Servants at Malang State Polytechnic (Polinema). Disproportionate stratified random sampling was used as a sampling technique. Then, data were anaysed by using Partial Least Square (PLS) with the Linkert scale as a measuring tool and SmartPLS 3.0 as a test tool. The results showed: (i) The implementation of management information systems has a significant effect on employee performance; (ii) have a significant effect on employee performance; (iii) The implementation of management information systems has a significant effect on motivation (iv) Rewards have a significant effect on motivation; (v) Motivation has a significant effect on employee performance; (vi) The application of management information systems has a significant effect on through motivation; (vii) Rewards have a significant effect on employee Rewards performance through motivation.